Genomic Landscape of Chinese Clear Cell Renal Cell Carcinoma Patients With Venous Tumor Thrombus Identifies Chromosome 9 and 14 Deletions and Related Immunosuppressive Microenvironment - Niu, Shaoxi; Liu, Kan; Xu, Yong; Peng, Cheng; Yu, Yao; Huang, Qingbo; Wu, Shengpan; Cui, Bo; Huang, Yan; Ma, Xin; Zhang, Xu; Wang, Baojun (Frontiers in Oncology, 2021)
Background: Clear cell renal cell carcinoma (ccRCC) with venous tumor thrombus (VTT) is associated with a poor outcome. Though multiple studies have widely depicted the landscape of genomic feature of ccRCC, the genetic profile of VTT along with its matched primary tumor has not fully elucidated. Materials and methods: Samples of VTT tissues, matched primary tumor tissues (n=25) and primary tumor tissues from ccRCC patients without VTT (n=25) were collected and analyzed using a whole-exome sequencing. Meanwhile, four additional ccRCC patients in our cohort who were unfit for surgery took anti-programmed death receptor-1 (PD-1) monoclonal antibody (Toripalimab, 240 mg, Q3W, IV). Results: Comparison of the primary kidney tumor from patients with VTT or not, a relatively higher prevalence of BAP1 and KDM5C alteration was found only in ccRCC with VTT, which was associated with a worse overall survival in the kidney renal clear cell carcinoma (KIRC) database. Meanwhile, as suggested by subclones, the VTT mainly originated directly from its primary renal mass. Significantly higher prevalence of CELSR2 and TET2 alterations was identified in the VTT compared with the matched primary tumor. Increasing prevalence of DNA damage repair genes, especially homologous recombination repair and non-homologous end joining were found in ccRCC with VTT group. Strikingly, VTT was characterized by the increase of copy number loss in whole exome (p<0.05), especially in the chromosome 9 and 14 region. Deletion of chromosome 9 and 14 was associated with a worse survival, unfavorable clinical features and immunosuppressive microenvironment characterized by higher infiltration of T cells regulators (Tregs), follicular helper T cells and resting mast cells but lower counts of resting CD4 memory T cells and CD8 positive T cells Three of four additional ccRCC patients with VTT in our center who tried anti-PD-1 therapy had remarkable remission in renal mass but no shrink in VTT. Conclusion: Our study revealed the genetic profile of Chinese ccRCC patients with VTT, and multiple known poor outcome features, including genetic alterations and copy number loss. The deletion in chromosome 9 and 14 and their related immunosuppressive microenvironment may indicate limited sensitivity to anti-PD-1/L1 monotherapy in VTT.